Electronic commerce : - Greenstein, Marilyn (McGraw-Hill /Irwin, 2002)
The field of electronic commerce has grown rapidly over the past few years. Major corporations and even small businesses are using electronic commerce as a channel of distribution. This growth has led to the need for business students to understand the security, risk management, and control issues related to electronic commerce.